Kemitraan Prodi DKV dan Sekolah untuk Meningkatkan Komunikasi Visual dalam Menciptakan Bahan Ajar - Wiraseptya, Tedy; Stefvany, Stefvany (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
Collaboration between the Visual Communication Design Study Program (DKV) and school educational institutions has become an interesting subject. This collaboration was carried out in an effort to improve the quality of teaching materials through improving visual communication. This research aims to explore and analyze collaboration between the DKV Study Program and schools in creating teaching materials that are more visually effective. This research method uses a qualitative method using a library research approach. The research results show the form of method steps in the collaboration process between the Visual Communication Design Study Program and schools. Then create a process flow in the collaborative activities that will be carried out later. Joint involvement in this development creates teaching materials, collaborative workshops and training for teachers on understanding visual design principles with learning needs in the school environment. This research campaigns for the importance of cross-sector collaboration in education to improve visual communication. An important implication of these results is the potential to have a better understanding of the process of developing more visually effective teaching materials through collaboration between DKV and schools, as well as providing a basis for further program development in improving the quality of education.